Studi Korelasi antara Pemberian Kompensasi dengan Kinerja Guru Pendidikan Agama Islam (PAI) di Kabupaten Minahasa Tenggara - Achmad Paturusi (Institut Agama Islam Negeri (IAIN) Manado, 2016)
The objective of this research is to obtain the empirical account of the correlation between compensation and performance of the Islamic Religious Education teachers in Kabupaten Minahasa, North Sulawesi. The population of this research is elementary school teachers. A sample of sixty respondents is drawn using a simple random sampling technique of Taro Yamane formula. Instruments used for the data collection are questionnaires on teachers’ performance and compensation. The data are analyzed employing a simple regression and partial correlation. This research finds out that a significant relationship between compensation and performance of the Islamic Religious Education teachers exists.